Netter's neuroscience coloring book - David L. Felten; Mary Summo Maida; Frank H. Netter (Philadelphia : Elsevier, 2019)
Reinforce your knowledge of neuroanatomy, neuroscience, and common pathologies of the nervous system with this active and engaging learn and review tool! Netter$1 (Bs Neuroscience Coloring Book by Drs. David L. Felten and Mary Summo Maida, challenges you to a better understanding of the brain, spinal cord, and peripheral nervous system using visual and tactile learning. It$1 (Bs a fun and interactive way to trace pathways and tracts, as well as reinforce spatial, functional, and clinical concepts in this fascinating field. More than "just" a coloring book, this unique learning tool offers:s
Keywords: Atlas; Neurophysiology; Nervous System Physiological Phenomena